Effect of Smart Pill Box on Improving Adherence to 6-Mercaptopurine Maintenance Therapy in Pediatric ALL - S. Abhilasha; Apoorva Bagalkotkar (Indian Journal of Medical and Paediatric Oncology)
Introduction 6-Mercaptopurine (6-MP) forms the backbone of maintenance chemotherapy for acute lymphoblastic leukemia (ALL). A Children's Oncology Group study found 3.9-fold increased risk of relapse in children with 6-MP adherence less than 90%.